Re-evaluating the effi cacy of the aqueous leaf extract of Bridelia ferrugenia and its potential combination with metformin in the management of diabetes mellitus - Dominic Adotei Edoh, Joseph A. Sarkodie, Ama Kyeraa Thomford, Kennedy Essuman, Derrick Owu, Kwesi Prah Thomford (Journal of Medicinal Herbs and Ethnomedicine, 2015)
Herbal medicinal products play a significant role in the management of diabetes and other chronic diseases either as a monotherapy or in combination with allopathic treatments. The hypoglycemic activity of a Ghanaian herbal antidiabetic product (Bridelia Tea) prepared from the dried leaves of Bridelia ferrugenia [BRD] was reevaluated in this study with the view of improving, its activity and explore the possible benefit of using the product in combination with metformin (MET). Male and female Sprague-Dawley rats (210-220 g) were rendered hyperglycemic by a single intraperitoneal administration of streptozocin (70 mg/kg) after an overnight fast. The hyperglycemic rats then received one of the following treatments ([BRD 30 mg/kg or 300 mg/kg], [MET 250 mg/kg or 1000 mg/kg], [MET 250 mg/kg and BRD 30 mg/kg], [MET 1000 mg/kg and BRD 300 mg/kg]). The hypoglycemic effect of BRD, MET, and the combination of the two products were not significantly different during an initial 6 h of monitoring (P > 0.05). In the long-term study over 28 days, BRD 300 mg/kg had hypoglycemic effects comparable to MET 1000 mg/kg p.o. and better than BDF 30 mg/kg p.o. (P < 0.05). However, the combination of the two products BRD and MET at the two doses reduced their therapeutic effect compared to animals receiving either one of the two treatments alone.